Fenomena Riverside Berbasis Kearifan Lokal Dalam Perspektif Komunikasi Pariwisata di Bohulo Camp - Akasse, Cahyadi Saputra; Subhan, Andi (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Local wisdom-based tourism is the application of a tourism concept that utilizes the potential that exists in the region. This implementation provides value for both tourist attraction managers and visiting tourists. Awareness of local wisdom-based tourist attractions needs to be considered because the tourism potential in the area needs to be increased. One application is to utilize riverside areas based on ecotourism, however this requires promotion through effective communication strategies so that it can reach a wider community through approaches in the media. This research aims to examine tourism communication strategies at Bohulo Camp and Eatery in increasing awareness of local wisdom-based tourist attractions and also in increasing tourists' interest in visiting. The method used in this research is qualitative with a case study approach. Data collection was carried out by observation and documentation. The research results show that the communication strategy carried out by the management of the Bohulo Camp and Eatery tourist attraction uses a social media approach and involves digital marketing agency services to manage promotional content on social media. The promotional technique is carried out by utilizing features from social media through the tagline #EscapeToNature which aims to attract tourists to travel in nature.